Constructing an Evaluation System of Education and Teaching Quality in Undergraduate Colleges and Universities Based on the DICE Framework - Wu, Yuan; Li, Ziwei (Economics & Management Review, 2024)
The digital transformation of education is a significant breakthrough in promoting the high-quality development of education and teaching quality in undergraduate colleges and universities. However, building an education and teaching quality evaluation system that adapts to the digital era has become an important issue that needs to be solved. Through literature combing and theoretical analysis, we explore the impact of digital transformation on the quality of education and teaching and construct a new system of education and teaching quality evaluation adapted to the digital era. It has been found that digital technology changes traditional teaching methods and learning environments and profoundly affects the connotation and evaluation standards of education quality. Based on this, this study proposes constructing an evaluation system for the quality of education and teaching in colleges and universities with the DICE framework, which covers four dimensions: digital foundation and strategy, integration and innovation, capacity building, and assessment and feedback. The system aims to comprehensively and accurately assess teaching quality, help the digital transformation of higher education, and provide theoretical guidance and practical reference.